Group eye movement desensitization and reprocessing interventions in adults and children: A systematic review of randomized and nonrandomized trials. (15th January 2021) - Kaptan, Safa Kemal; Dursun, Busra Ozen; Knowles, Mark; Husain, Nusrat; Varese, Filippo
Abstract: This review systematically synthesized existing literature on group protocols of eye movement desensitization and reprocessing (EMDR) therapy for treating a range of mental health difficulties in adults and children. We conducted database searches on PsychINFO, EMBASE, MEDLINE, Web of Science, The Cochrane Library and Francine Shapiro Library up to May 2020, using PRISMA guidelines. Studies were included if they used at least one standardized outcome measure, if they present a quantitative data on the effect of group EMDR protocols on mental health difficulties and if they were published in English. Twenty‐two studies with 1739 participants were included. Thirteen studies examined EMDR Integrative Group Treatment Protocol (IGTP), four studies examined EMDR Group Traumatic Episode Protocol (G‐TEP), four studies EMDR Integrative Group Treatment Protocol for Ongoing Traumatic Stress and one study considered EMDR Group Protocol with Children. Of the 22 studies included, 12 were one‐arm trials and 10 were two‐arm trials. We assessed risk of bias using a revised Tool to Assess Risk of Bias in Randomized Trials (ROB 2) and Risk of Bias in Nonrandomized Studies of Interventions (ROBINS‐I). Overall, the results suggested that Group EMDR protocols might be an effective tool in improving a wide range of mental health‐related outcomes including posttraumatic stress disorder (PTSD), depression and anxiety. However, the included studies are limited to methodological challenges. The limitations and future directions are discussed.